Precise surface gravities of δ Scuti stars from asteroseismology. (22nd July 2017) - García Hernández, A.; Suárez, J. C.; Moya, A.; Monteiro, M. J. P. F. G.; Guo, Z.; Reese, D. R.; Pascual-Granado, J.; Barceló Forteza, S.; Martín-Ruiz, S.; Garrido, R.; Nieto, J.
Abstract: The work reported here demonstrates that it is possible to accurately determine surface gravities of δ Scuti (δ Sct) stars using the frequency content from high-precision photometry and a measurement of the parallax. Using a sample of 10 eclipsing binary systems with a δ Sct component and the unique δ Sct star discovered with a transiting planet, WASP-33, we were able to refine the Δν–$\bar{ρ }$ relation. Using this relation and parallaxes, we obtained independent values for the masses and radii, allowing us to calculate the surface gravities without any constraints from spectroscopic or binary analysis. A remarkably good agreement was found between our results and those published, extracted from the analysis of the radial velocities and light curves of the systems. This reinforces the potential of Δν as a valuable observable for δ Sct stars and settles the degeneracy problem for the log g determination through spectroscopy.